COMMUNITY-RELATED FACTORS INFLUENCING GENDER INEQUALITY IN NURSING PROFESSION, A CROSS-SECTIONAL STUDY AMONG NURSES AND STUDENT NURSES FROM SELECTED HOSPITALS AND NURSES TRAINING INSTITUTIONS IN NORTHERN UGANDA. - Lilly Grace Lalam; Florence Nabushawo Oketcho (Student's Journal of Health Research, 2023)
Introduction: The striking level of gender inequality (GI) in the nursing profession (NP) is also influenced by community-related factors. 81.3% of preferences and choices for NP were determined by gender roles. Caring and nurturing (64.2%) were the major female gender roles associated with nursing, a potential reason for 73.6% of female nurses.   Patients/attendants and staff calls female nurses "sisters", a traditional concept associated with their communal gender roles. Various individuals are nurses for different community-motivating reasons. Largely, 36.1% of rude nurses, possibly intervene. Community male nurses' perception discourages most males from the female-dominated profession.  Friends/peers are the leading community perpetrator of GI in NP.  The main study objective was to determine factors influencing gender inequality in the nursing profession among nurses and student nurses in the selected hospitals and nurses training institutions in the northern cities of Uganda.  Methodology: A cross-sectional study design was used to obtain quantitative data from respondents. Trained research assistants acquired raw data using a pretested structured English questionnaire. Data were single-entered and analyzed using statistical software version 26. Study variables were described using Frequency tables and graphs. Univariate and bivariate analysis methods were used to identify factors associated with GI. Variables with a P-value of <0.05 with a 95% confidence interval were used to declare statistical significance.  Results: 95.6% of responses were achieved. Community gender challenge for Becoming a Nurse (X 2=17.907, p-0.000) was significantly associated with GI in NP. Friends/peers are the main community perpetrator of gender discrimination (42.4%). Academic failures (32.1%) and doctors (29.5%) were the foremost community perception of male nurses.   Conclusion:  Family and community support is key to gender equality in NP for the achievement of SDGs and health targets. Recommendation: More research is needed to strengthen policies in the NP.